2014
DOI: 10.1080/15402002.2014.974182
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Sleepiness Is Associated With Reduced Integration of Temporally Distant Outcomes on the Iowa Gambling Task

Abstract: Sleep deprivation is associated with performance decrements on some measures of executive functioning. For instance, sleep deprivation results in altered decision making on the Iowa Gambling Task. However, it is unclear which component processes of the task may be driving the effect. In this study, Iowa Gambling task performance was decomposed using the Expectancy-Valence model. Recent sleep debt and greater daytime sleepiness were associated with higher scores on the updating parameter, which reflects the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…It would be interesting to discern risk taking from risk learning to see whether risky behaviour with negative outcomes in a real-life setting has less of an impact on future decisions when sleep has been restricted. People who are sleepy may also have a shorter learning span, such that they use more recent information rather than learning from information from longer ago 33 .…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to discern risk taking from risk learning to see whether risky behaviour with negative outcomes in a real-life setting has less of an impact on future decisions when sleep has been restricted. People who are sleepy may also have a shorter learning span, such that they use more recent information rather than learning from information from longer ago 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This would further contribute to non-optimal reward-dependent decision making and actions. Fitting this profile, sleep-deprived individuals performing the Iowa Gambling Task make more-risky decisions and assign greater weights to more-recent rewards 45,46 . This pattern indicates a failure to appropriately integrate rewards and their accumulating value over time following SD, reflecting temporally shorter -sighted updating of rewards.…”
Section: Reward and Incentive Processingmentioning
confidence: 99%
“…Recent studies have shown that persistence when waiting for an event to occur is strongly dependent upon expectations of the delay duration (McGuire and Kable, ) Decision‐makers adjust their persistence dynamically based on the experienced statistical distribution of delays (McGuire and Kable, ). Relevant to the present work, insufficient sleep can affect decision‐making negatively by impairing our ability to integrate prior outcome information accurately into later decisions (Olson et al ., ; Whitney et al ., ). However, whether or not the ability to calibrate persistence based on experienced delays is affected by sleep deprivation has not been studied previously.…”
Section: Introductionmentioning
confidence: 99%